1995
DOI: 10.1177/875647939501100205
|View full text |Cite
|
Sign up to set email alerts
|

B-Mode Ultrasound Evaluation of Dolphin Skin

Abstract: Skin specimens from 10 dolphins were studied with B-mode ultrasonography. The epidermal and hypodermal layers were defined, measured, and compared with measurements of actual tissue and with histologic measurements. Measurements of skin from six body zones of three live dolphins showed larger values but the same echogenic characteristics. B-mode measurements were found to be accurate and to provide visually acceptable information for use in evaluating the health status of these animals. The detection of a skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Several recent articles (e.g. [12,[16][17][18][19][20]) have however presented more authoritative, detailed measurements and analyses. These are now being used for Finite-Element investigations using ANSYS, and looking at the entire structure of the dolphin's jaw.…”
Section: Discussion -Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent articles (e.g. [12,[16][17][18][19][20]) have however presented more authoritative, detailed measurements and analyses. These are now being used for Finite-Element investigations using ANSYS, and looking at the entire structure of the dolphin's jaw.…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…The construction of an accurate 3-D model of a dolphin's jaw is made possible by recent advances in measurements of the acoustically-related properties of its constituents (e.g. [12,[16][17][18][19][20]) and in understanding sound production in dolphins and whales [16]. Section 2 showed the importance of the exact position of each tooth, and of its diameter variations (e.g.…”
Section: -D Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound is an alternative way to measure blubber thickness that have showed to correlated with direct measurement (Cartee et al, 1995;Zeng et al, 2015). It relies on the concept of sound travelling at different speeds through tissues of different density (Curran and Asher, 1974).…”
Section: Ultrasound Measurementmentioning
confidence: 99%
“…For example Cornick et al (2016), reported a mean measurement bias of 0.20 cm between ultrasound and rule data, in belugas. The method has been successfully applied to captive harbour porpoises (Kastelein et al, 1995), bottlenose dolphins (Cartee et al, 1995) and gray whale (Eschrichtius robustus) (Curran and Asher, 1974). The pre-requisite of restraint during measurement however limits its application to small cetaceans and similarly places limitations on the number of animals that can feasibly be assessed.…”
Section: Ultrasound Measurementmentioning
confidence: 99%